Barriers to Medical Tourism Development in the United Arab Emirates (UAE) - Bulatovic, Iva (Int J Environ Res Public Health, 2021)
Medical tourism is a thriving industry. Many destinations now seek to attract more medical tourists. The United Arab Emirates (UAE) is no exception. As one of the most important pillars of the UAE’s economy, tourism is considered a high priority. However, medical tourism in the UAE is still developing. This paper addresses the main challenges for medical tourism in the UAE and proposes methods to enhance its development. This research utilized qualitative analysis. Twelve professionals in medical tourism were interviewed to provide data. The data were then analyzed using NVivo 12 software. Our results indicate that the key barriers to medical tourism development in the UAE are high costs of medical tourism services, lack of marketing activities, lack of collaboration between medical and tourism service providers, and so forth. Although initiatives from the UAE government are very encouraging, more efficient medical care supply networks, tourism suppliers and intermediaries should be established to ensure its growth. This research could influence national tourism policies in the UAE as well as regional alliances in all Gulf Cooperation Council (GCC) and the Middle East and North Africa (MENA) countries.